2006
DOI: 10.1063/1.2195896
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributions of trapping centers in HfO2∕SiO2 gate stacks

Abstract: A methodology to analyze charge pumping (CP) data, which allows positions of probing traps in the dielectric to be identified, was applied to extract the spatial profile of traps in SiO2∕HfO2 gate stacks. The results suggest that traps accessible by CP measurements in a wide frequency range, down to few kilohertz, are located within or near the interfacial SiO2 layer rather than in the bulk of the high-k film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 14 publications
5
35
0
Order By: Relevance
“…Low frequency CP measurements were shown to probe the defects spatially distributed deep into IL [17]. Young et al showed that the probing depth of CP frequency in kHz order is around 1.2 nm from the IL/Si interface [11].…”
Section: Resultsmentioning
confidence: 99%
“…Low frequency CP measurements were shown to probe the defects spatially distributed deep into IL [17]. Young et al showed that the probing depth of CP frequency in kHz order is around 1.2 nm from the IL/Si interface [11].…”
Section: Resultsmentioning
confidence: 99%
“…These changes are believed to be caused by the HfO 2 / SiO 2 interface charge. 18,19 The stack measured in the experiment may be simplified to a system with two insulators with different dielectric constants and two charge densities localized at the HfO 2 / SiO 2 and SiO 2 / SiC interfaces, respectively. Considering a flatband condition, it can be shown from Gauss law that E ox = ox / ox and E HfO 2 = ͑ ox + HfO 2 ͒ / HfO 2 .…”
Section: B Capacitance-voltage Characteristics Of Sic Samplesmentioning
confidence: 99%
“…In our investigation of an interfacial layer we have concentrated on an SiO 2 interfacial layer. This is justified by a number of different studies [20][21][22] which have shown that the interfacial layer between Si and Hf oxide consists of a SiO 2 layer or in general a SiO x type layer, and any diffusion of Hf into the interfacial layer is only minor and occurs only at the very edge of the interfacial layer with Hf. However, as yet there are very little data on the stoichiometric content (x value) of the SiO x layer, we have assume an SiO 2 interfacial layer.…”
Section: The Role Of the Interfacial Layermentioning
confidence: 96%